Stereospecific control of microbial growth by a combinatoric suite of chiral siderophores - Parker R. Stow; Kiefer O. Forsch; Emil Thomsen; Hiroaki Naka; Margo G. Haygood; Katherine A. Barbeau; Alison Butler (Proceedings of the National Academy of Sciences, 2025)
Bacteria compete for iron by producing small-molecule chelators known as siderophores. The triscatechol siderophores trivanchrobactin and ruckerbactin, produced by Vibrio campbellii DS40M4 and Yersinia ruckeri YRB, respectively, are naturally occurring diastereomers that form chiral ferric complexes in opposing enantiomeric configurations. Chiral recognition is a hallmark of specificity in biological systems, yet the biological consequences of chiral coordination compounds are relatively unexplored. We demonstrate stereoselective discrimination of microbial growth and iron uptake by chiral Fe(III)–siderophores. The siderophore utilization pathway in V. campbellii DS40M4 is stereoselective for Λ-Fe(III)–trivanchrobactin, but not the mismatched Δ-Fe(III)–ruckerbactin diastereomer. Chiral recognition is likely conferred by the stereospecificity of both the outer membrane receptor (OMR) protein FvtA and the periplasmic binding protein (PBP) FvtB, both of which must interact preferentially with the Λ-configured Fe(III)-coordination complexes.